National Health Service breast screening programme results for 1991-2. Issue 6900 (7th August 1993) - Chamberlain, J; Moss, S M; Kirkpatrick, A E; Michell, M; Johns, L
Abstract : OBJECTIVES–To report the results of the NHS breast screening programme for the year March 1991 to April 1992. DESIGN–A report of statistics was derived from Körner (K62) returns and from the radiology quality assurance programme. MAIN OUTCOME MEASURES–Detection rates for breast cancer and small (< or = 10 mm diameter) invasive cancer, benign biopsy rates, and recall and acceptance rates. RESULTS–The acceptance rate for screening across the United Kingdom was 71.3%. The referral rate for further investigation was 6.2% (regional 4.3-9.0%). The breast cancer detection rate was 6.2 cancers per 1000 women screened (5.1-9.0) and the detection rate of invasive cancers < or = 10 mm was 1.4/1000 (1.0-2.3). 72% of screening programmes reached the target 70% acceptance rate, and 95% of programmes achieved a recall rate of less than 10%. 75% of programmes had a cancer detection rate of more than 5/1000, but only 32% had a detection rate for invasive cancers < or = 10 mm of more than 1.5/1000. CONCLUSIONS–Overall, the results of the screening programme for the year 1991-2 can be regarded as extremely satisfactory, given the size and complexity of the operation.